Impacts of light illumination on monocrystalline silicon surfaces passivated by atomic layer deposited Al2O3 capped with plasma-enhanced chemical vapor deposited SiNx. (30th June 2017) - Lin, Fen; Toh, Mei Gi; Thway, Maung; Li, Xinhang; Nandakumar, Naomi; Gay, Xavier; Dielissen, Bas; Raj, Samuel; Aberle, Armin G.
Abstract: In this work, we investigate the impact of light illumination on crystalline silicon surfaces passivated with inline atomic layer deposited aluminum oxide capped with plasma-enhanced chemical vapor deposited silicon nitride. It is found that, for dedicated n-type lifetime samples under illumination, there is no light induced degradation (LID) but enhanced passivation. The lifetime increase happened with a much faster speed compared to the lifetime decay during dark storage, resulting in the overall lifetime enhancement for actual field application scenarios (sunshine during the day and darkness during the night). In addition, it was found that the lifetime enhancement is spectrally dependent and mainly associated with the visible part of the solar spectrum. Hence, it has negligible impact for such interfaces applied on the rear of the solar cells, for example p-type aluminum local back surface field (Al-LBSF) cells.